Gambaran pola pemberian makan pada balita dengan risiko stunting - Azira, Zahwa; Hartaty, Neti; Atika, Syarifa (Indonesian Journal of Health Science, 2025)
Background: Stunting remains a major global public health concern, particularly in early childhood, as it is closely related to inadequate nutritional intake and feeding patterns. Aim Of Research: This study aimed to describe the feeding patterns of toddlers at risk of stunting, where the risk of stunting was determined by the absence of complete exclusive breastfeeding. Methode: This research employed a descriptive quantitative design with a cross-sectional approach. The study involved 103 respondents selected through non-probability sampling using purposive sampling. The participants were mothers with toddlers aged 1–5 years who had a history of incomplete exclusive breastfeeding. Result: The findings revealed that the feeding patterns of toddlers at risk of stunting in Meuraxa District, Banda Aceh, were categorized as appropriate in 73 respondents (70.9%), which included appropriate food types in 100 respondents (97.1%) and appropriate feeding schedules in 81 respondents (78.5%). However, 59 respondents (57.3%) had inappropriate feeding schedules. Conclusion: In conclusion, the feeding patterns in Meuraxa District, Banda Aceh, were generally appropriate in terms of food type and quantity, while feeding schedules were categorized as inappropriate. It is recommended that the Meuraxa Community Health Center provides education on proper feeding practices for toddlers. Latar Belakang: Masalah stunting merupakan masalah gizi balita yang hingga saat ini masih menjadi fokus dunia, dimana stunting adalah masalah pemenuhan gizi yang berkaitan erat dengan pola pemberian makan pada balita. Tujuan: tujuan penelitian ini untuk mengetahui gambaran pola pemberian makan pada balita dengan risiko stunting, dimana risiko stunting sendiri diukur dari faktor pemberian ASI eksklusif tidak lengkap. Metode: Penelitian ini menggunakan jenis penelitian deskriptif dengan metode kuantitatif melalui pendekatan cross-sectional dengan responden sebanyak 103 responden yang dipilih melalui metode non-probability sampling dengan teknik pengambilan sampel yaitu purposive sampling, yang memiliki kriteria ibu yang memiliki balita usia 1-5 tahun, serta riwayat ASI eksklusif tidak lengkap. Hasil: Hasil dari penelitian ini yaitu pola pemberian makan balita dengan risiko stunting di Kecamatan Meuraxa Kota Banda Aceh memiliki kategori tepat sebanyak 73 orrang (70,9%) yang meliputi jenis sebanyak 100 orang (97,1%) dan jadwal sebanyak 81 orang atau (78,5%), sedangkan pada jadwal pemberian makan memiliki kategori tidak tepat sebanyak 59 orang (57,3%). Kesimpulan: Kesimpulan penelitian ini yaitu pola pemberian makan di Kecamatan Meuraxa Kota Banda Aceh memiliki kategori tepat, baik jenis maupun jumlah makan, sedangkan pada jadwal makan memiliki kategori tidak tepat, diharapkan kepada pihak Puskemas Meuraxa agar dapat memberikan edukasi terkait pola pemberian makan pada balita.